تداعیات ظاھرة الفساد المالي والاداري على حقوق الانسان في العراق (Journal of the College of Education for Women, 2019)
The kinds of financial and administrational corruption have an importantdimensions and affects on human rights because of all events which happened in the worldmade tackles concerning with this phenomena.This article has been researched about an impacts of it to the nature of structuralsocial system especially its scopes items in institutionally and politically and economicallyand culturally to be an obvious in all fields.This phenomena should be studied carefully in order to put all remedies requiredfor set up with measures and procedures such as following :1-the dependency on respecting all laws in the country.2-the work with principles of accountability transparency in pro-active cooperation level.3- activating judicial measures to change life-style of manners for everybody make forresponsibility in the institutions of the state.4- enlarging extents of another institutionscensorship by depending on an important elements to regulating resources- of expendituresin the state.Therefore- we must follow up nature of eradicating all kinds of corruption in order torespect totally dimensions human rights in Iraq.